Thromboelastometry for Assessing Risks of Free Flap Thrombosis in Patients Undergoing Microvascular Surgery - Vanags, Indulis (Front Med (Lausanne), 2020)
Introduction: Coagulation assessment is often missing in microvascular surgery. We aimed at evaluating the predictive value of thromboelastometry for free flap thrombosis in microvascular surgery patients. Materials and Methods: We enrolled 103 adult patients with traumatic injuries scheduled for microvascular free flap surgery into a prospective observational study. Thirty-six patients with recent trauma underwent surgery within 30 days (ES group), and were compared with 67 trauma patients who underwent surgery later than 30 days (late surgery, LS group) after the injury. Rotational thromboelastometry (RTE) was performed before surgery. Functional fibrinogen to platelet ratio (FPR) ≥ 42 was selected as the main hypercoagulability index. Free flap thrombosis was set as primary outcome. Thrombotic risk factors and duration of surgery related to free flap thrombosis were secondary outcomes. Statistical significance p < 0.05; not significant NS. Results: Six patients (16.7%) in the ES group and 10 (14.9%) in the LS group had free flap thrombosis (NS). In the entire cohort, free flap thrombosis rate increased in the presence of thrombogenic comorbidities (OR 4.059, CI 1.33–12.37; p = 0.014) and prolonged surgery times (OR 1.007, CI 1 – 1.012; p = 0.05). Although hypercoagulability occurred more frequently in the ES group (44.4%) than in the LS group (11.9%; p < 0.001), it was not associated with higher free flap thrombosis rate. In ES group patients with surgery times > 240 min, the risk of free flap thrombosis increased (OR 3.5, CI 1.16-10.6; p = 0.026) with 93.3% sensitivity and 86.7% specificity (AUC 0.85; p = 0.007). In contrast, in LS patients hypercoagulability increased the odds of free flap thrombosis (OR 8.83, CI 1.74–44.76; p = 0.009). Moreover, a positive correlation was found between FPR ≥ 42 and free flap thrombosis rate (r = 0.362; p = 0.003). In the LS group, the presence of thrombogenic comorbidities correlated with free flap thrombosis rate (OR 7, CI 1.591–30.8; p = 0.01). Conclusions: In LS patients with thrombogenic comorbidities, thromboelastometry supports the detection of hypercoagulability and predicts free flap thrombosis risk. In ES patients, postoperative hypercoagulability did not predict free flap thrombosis. Prolonged surgery time should be considered as a risk factor.